Sexual Behaviors During the Covid-19 Pandemic: Social Representations of Gay and Heterosexual Men - de Oliveira Santos, José Victor (2022)
Objective. This article aimed to compare the social representations between groups of gay and heterosexual men about sexual behavior as a result of social isolation from the Covid-19 pandemic. Method. 200 men participated (100 heterosexuals and 100 homosexuals) with average age of 27.06 and 28.12, respectively. A sociodemographic questionnaire was used for sample characterization and a semi-structured interview for the apprehension of SR, with data processed by the IRAMUTEQ software. Results. Similarities were found in both groups in terms of active sex life and the use of technologies for sexing and access to pornography. However, homosexuals diverge in the representational structure when seeking greater compensatory strategies for having more stable civic states. It is concluded that physical distance reveals heterogeneous intercurrences to affective-sexual life in this new social reality.